2005
DOI: 10.1093/toxsci/kfj064
|View full text |Cite
|
Sign up to set email alerts
|

Potent Neurotoxic Action of the Shellfish Biotoxin Yessotoxin on Cultured Cerebellar Neurons

Abstract: Yessotoxin (YTX) and its analogues are disulphated polyether compounds of increasing occurrence in seafood. The biological effects of these algal toxins on mammals and the risk associated to their ingestion have not been clearly established. We have used primary cultures of rat cerebellar neurons to investigate whether YTX affected survival and functioning of central nervous system neurons. Exposure to YTX (> or =25 nM) caused first (approximately 8 h) weakening, granulation, and fragmentation of neuronal netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 34 publications
(62 reference statements)
2
35
0
Order By: Relevance
“…Thus, the changes in the cytoplasmic Ca 2+ concentration may induce the process of apoptosis (32,33). Previous studies indicated that YTX may induce the increase of Ca 2+ levels in several types of cells (22,23,26). Our previous studies also demonstrated that YTX may induce Ca 2+ entry in different types of human cells (21,34).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, the changes in the cytoplasmic Ca 2+ concentration may induce the process of apoptosis (32,33). Previous studies indicated that YTX may induce the increase of Ca 2+ levels in several types of cells (22,23,26). Our previous studies also demonstrated that YTX may induce Ca 2+ entry in different types of human cells (21,34).…”
Section: Discussionmentioning
confidence: 82%
“…YTX is a low-molecular weight compound that is toxic to different mammalian and insect cell types, including cancer cells (14,15,(23)(24)(25)(26). Our previous studies demonstrated the apoptosis induced by YTX in HeLa human cervical cancer cells, Bel7402 human hepatocellular carcinoma cells and HL7702 human liver cells (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Perez-Gomez et al described an IC 50 of 20 nM in cerebellar granule neurons, 28 but lower doses induced also toxicity signals. We show in the present work that primary cortical neurons are more sensitive to YTX toxicity than the neurons used in the previous study, setting the IC 50 for these cells in 4.27 nM.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The chemical structure of YTX is similar to that of the neurotoxic brevetoxins, and interactions between YTX and transmembrane ion channels have been studied (20,21). Furthermore, YTX has been identified as an inducer of apoptosis in the BE (2)-M17 neuroblastoma cell line (22), in primary neuronal cultures (21), in myoblast cell lines from rat and mouse (23,24) and in the HeLa human cervical cancer cell line (25). However, the exact molecular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%